Clinics in diagnostic imaging (48). Cystic liver metastases - Muttarak M. (2014)
A 51-year-old man presented with an epigastric mass. Ultrasonography showed multiple cystic liver masses due to metastases from transitional cell carcinoma. Causes of cystic liver lesions include simple cyst, polyeystic liver disease, abscess, choledochal cyst, biliary cysadenoma and cystadenocarcinoma, and primary liver tumour. The imaging features of various types of cystic liver lesions are reviewed.